Using the systemic-resilience thinking approach to enhance participatory collaborative management of natural resources in tribal communities: Toward inclusive land reform-led outdoor tourism. (March 2019) - Musavengane, Regis
Abstract: Community participation is at the heart of environmental governance as it facilitates and promotes a sense of ownership in a society's decision making and social development issues. This paper, using both primary and secondary data collected through methods inspired by participatory research, set out to discuss a methodological approach aimed at understanding how common pool natural resources are managed by multi-actors and stakeholders in a developing country context in an effort to promote inclusive land reform-led outdoor tourism. It combines two 'soft-systems' schools of thought, systemic thinking and resilience thinking, to analyse the effectiveness and efficiency of collaborative management of natural resources in tribal communities established through land reform processes in South Africa. It is argued in the paper that the two schools of thought can play key roles in identifying and informing the development of appropriate intervening measures and strategies that can contribute towards the adoption of effective and sustainable systems of community natural resource management and bring about more meaningful community development through community-based tourism. These observations have been made within the broader and contemporary arguments of sustainable environmental management and community development. Management implications: The systemic-resilience approach appears to be critical for increasing stakeholder participation in conservation endeavours aimed at outdoor recreational activities and tourism. The intervention approach in complex tribal communities is key for establishing accommodations that will enable developing action plans to enhance stakeholder participation in co-managing common pool natural resources earmarked for community-based ecotourism. The systemic-resilience approach promotes strong and genuine grassroot-grown community participation in environmental management decision making, thereby promoting stakeholder participation of interested actors in outdoor recreation and tourism. Systemic-resilience facilitates the attainment of social capital elements which are key to the successful co-management of natural resources, i.e. participation, transparency, reciprocity and effective communication.